Where does Sedum cepaea L. (Crassulaceae) – one of the rarest species of Croatian flora – really grow? - Sapic, Irena; Segota, Vedran; Alegro, Antun (Acta Botanica Croatica, 2012)
The distribution of Sedum cepaea in Croatia is limited to sciophilous or slightly heliophilous forest habitats in the zone dominated by Quercus petraea, developed on acidic types of soil above siliceous bedrock.We confirm a finding spot on Moslavacka gora and describe new localities on Zrinska gora (central Croatia). Two S. cepaea populations on Nikolino brdo [hill] in Topusko disappeared a century ago.